Marley Dias gets it done : and so can you! - Dias, Marley (Marley Emerson); McGowan, Siobhán (Scholastic Press, 2018)
Examines the life of social media celebrity and social activist Marley Dias, offering advice from Marley on how to become "woke" to social injustices and how to start making a difference to society.